PENERAPAN SLOW DEEP BREATHING EXERCISE SEBAGAI UPAYA PENCEGAHAN PENINGKATAN HIPERTENSI DI KECAMATAN JEBRES SURAKARTA - Ria Nurdiana Sugita; Aliza Berliana Syaharani; Natasya Eskadevi Irawan; Dita Mirawati (Empowerment Journal, 2022)
Hypertension or commonly referred to as high blood pressure is a non-communicable disease where the working conditions of the blood vessels work with strong pressure. Hypertension is also called the silent killer because the symptoms are not obvious. The highest prevalence of hypertension occurs at the age of 55-64 years with a percentage of 55.2% and the lowest at the age of 18 years with a percentage of 34.1%. In the area of RT 02 RW 12, Jebres District, hypertension is the most common disease. To deal with this, hypertension counseling and Slow Deep Breathing Exercise training were carried out as an effort to reduce the increase in hypertension. Slow Deep Breathing Exercise is an exercise that is used to reduce the level of increased hypertension by taking a deep breath in with the stomach inflated and exhaling slowly through the lips by contracting the stomach. The results obtained from hypertension counseling activities and Slow Deep Breathing Exercise training, the community of RT 02 RW 12 Jebres District became educated and had non-pharmacological solutions to reduce hypertension.